Use of Satellite Imagery for Banyuwangi Lampon Beach Tourist Road Track Planning - Ghoni, Abdul; Sukmawati, Sri; Soetjipto, Jojok Widodo (Rekayasa Sipil, 2024)
Transportation is a crucial element in the development of an area, especially in the context of developing transportation routes in Lampon Beach, Banyuwangi Regency. With inadequate road access, the development of road routes on this beach is a priority to increase the region's economic productivity by utilizing the potential of natural resources. This research applied the spatial data-based Technology-Based Integration Method with the support of ArcGIS and Civil 3D software. Two road traces were generated, with the total length of trace 1 is 4.76 km and trace 2 is 4.98 km; the volume data of trade 1 with excavation amounted to 52,064.09 m3, and embankment amounted to 15,002.59 m3. Meanwhile, the volume of trade 2 with excavation amounted to 89,464.92 m3, and the barrier amounted to 12,537.02 m3. These results demonstrate the efficiency and accuracy of infrastructure planning on the geographical and spatial characteristics of the region. The assessment of excavation and embankment costs provides an overview of the resources required by applicable standards and regulations. This approach contributes significantly to selecting efficient road routes and a better understanding the resources needed for infrastructure development.